Reducing poverty and hunger through food policy research: Highlights IFPRI and USAID partnership - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
For four decades, the longstanding collaboration between the United States Agency for International Development (USAID) and the International Food Policy Research Institute (IFPRI) has been crucial to helping developing countries attain agriculture-led economic growth. The innovative programs and strong evidence base produced through this partnership have contributed to transforming policies and investments for improved food security, nutrition, incomes, and resilience around the world.